PREDICTING SURVIVAL AND DEATH OF MICROBIAL PATHOGEN ASSOCIATES IN THE PRESENCE OF LECTINS OF PROBIOTICS: SIGNIFICANCE FOR THERAPY - M. V. Lakhtin; S. S. Afanasiev; V. M. Lakhtin; V. A. Aleshkin (Acta Biomedica Scientifica, 2012)
Developed by us conception of micropathogen associate acting like communicative organism was proposed. It allows predicting some pathogen responses to the presence of systemic localized lectins of probiotics. The rules of eukaryotic pathogen behavior in the presence of cascade probiotic lectins are formulated. New criteria of pathogenicity are described. The data will provide understanding the relationships of microbiota in biotopes as well as constructing directed space cascades of microbiocenose landscapes for medical biotechnology.